(untitled) (Comprehensive Journal of Science, 2025)
In the present work, two types of polymers are polystyrene (PS) and polydimethylsiloxane (PDMS) were used, where Molecular weight of polymers can be determined by different techniques such as intrinsic viscosity measurement. Determination of molecular weight by intrinsic viscosity measurement is a simple method for characterization of polymers. Different concentrations of polymers were prepared and measurement was done at room temperature. The flow time data was used to calculate the intrinsic viscosity by extrapolating the reduced viscosity to zero concentration. The value of intrinsic viscosity was then recalculated into the viscosity-average molecular weight using Mark-Houwink equation. The results were obtained to calculate the viscosity average molecular weight of both types of polymers respectively, PS is (97,223.05) and PDMS is (100,359.98) and are considered good results.